Occurrence and Risk Factors of Adverse Drug Reactions in Patients Receiving Bivalirudin as Anticoagulant During Percutaneous Coronary Intervention: A Prospective, Multi-Center, Intensive Monitoring Study - Li, Ping; Zhang, Hongyan; Luo, Caidong; Ji, Zheng; Zheng, Zeqi; Li, Zhenyong; Wu, Fan; Li, Jinlong; Hong, Lang (Frontiers in Cardiovascular Medicine, 2022)
Background: Bivalirudin is a common anticoagulant during percutaneous coronary intervention (PCI); however, since its application in China, it still lacks comprehensive evaluation of adverse events (AEs) or adverse drug reactions (ADRs) under the real-clinical setting conditions with a large-sample-size population. Therefore, this prospective, multi-center, intensive monitoring study aimed to comprehensively investigate the occurrence and risk factors of AEs and ADRs during PCI with bivalirudin as anticoagulant. Methods: Totally 3049 patients who underwent PCI with bivalirudin as anticoagulant from 27 Chinese medical centers were enrolled. Safety data (AEs/ADRs) were collected from hospital admission to 72 hours after bivalirudin administration; then, patients were followed up at the 30th day with the safety data collected as well. Results: 414 (13.58%) patients occurred AEs, among which 31 (1.02%) cases suffered from severe AEs and 8 (0.26%) cases died due to AEs. Importantly, 118 (3.87%) patients occurred bivalirudin related ADRs, among which 7 (0.23%) cases suffered from severe ADRs while no case (0%) died due to ADRs. Of note, 7 (0.23%) patients showed new ADRs, 34 (1.12%) patients experienced bleeding, 79 (2.59%) patients had thrombocytopenia. Furthermore: age, renal function impairment, CRUSADE high risk stratification independently correlated with total ADRs risk; CRUSADE high risk stratification, emergency operation, full dose bivalirudin independently associated with bleeding risk; age, renal function impairment independently related to thrombocytopenia risk. Conclusion: Bivalirudin is well tolerated as anticoagulant for PCI procedure; meanwhile, older age, renal function impairment and CRUSADE high risk stratification serve as independent risk factors of bivalirudin related ADRs.